Nursing Management and Professional Concepts - Open RN, Open Resources for Nursing (Open textbook library., 2022)
This book introduces concepts related to nursing leadership and management, prioritization strategies, delegation and supervision, legal implications of nursing practice, ethical nursing practice, collaboration within the interprofessional team, health care economics, quality and evidencebased practice, advocacy, preparation for the RN role, and the avoidance of burnout with self-care. Several online, interactive learning activities are included in each chapter that encourage application of content to patientcare situations. Additionally, the Appendix includes a “suite of patients” with suggested prompts for classroom discussion to assist students in applying concepts from the book to real patient-care situations.